Revealing Calcium Signaling Pathway as Novel Mechanism of Danhong Injection for Treating Acute Myocardial Infarction by Systems Pharmacology and Experiment Validation - Guo, Siyu; Tan, Yingying; Huang, Zhihong; Li, Yikui; Liu, Weiyu; Fan, Xiaotian; Zhang, Jingyuan; Stalin, Antony; Fu, Changgeng; Wu, Zhishan; Wang, Penglong; Zhou, Wei; et al. (Frontiers in Pharmacology, 2022)
Abstract Introduction: Danhong injection (DHI) is a traditional Chinese medicine preparation commonly used in the clinical treatment of acute myocardial infarction (AMI). In this study, the active components of DHI and its mechanism in the treatment of AMI were investigated. Methods: The chemical components of DHI were detected by the ultra-high-performance liquid chromatography-linear trap quadrupole-orbitrap-tandem mass spectrometry (UHPLC-LTQ-Orbitrap-MS/MS), and the targets and pathways of DHI in the treatment of AMI were analyzed by systems pharmacology, which was verified by molecular docking and animal experiments. Results: A total of 12 active components of DHI were obtained, and 158 common targets of component and disease were identified by systems pharmacology. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis results showed that DHI is closely related to the calcium signaling pathway in the treatment of AMI. Molecular docking showed that the key target protein has good binding affinity to related compounds. The experimental results showed that compared with the model group, LVAWs, EF, and FS significantly (P<0.05) increased in the DHI group. The percentage of myocardial infarction significantly (P<0.01) decreased, both in the ventricular and total cardiac regions, and the pathological damage of myocardial tissue also decreased. In addition, the expression of the protein CaMK II decreased (P<0.01) and the expression of SERCA significantly increased (P<0.01). Conclusion: This study revealed that ferulic acid, caffeic acid and rosmarinic acid could inhibit AMI by regulating PLB, CaMK II, SERCA, etc. And mechanistically, calcium signaling pathway was critically involved. Combination of systems pharmacology prediction with experimental validation may provide a scientific basis for in-depth clinical investigation of the material basis of DHI.